The Influence of Human Resource Competence, Leadership Style, and Communication Systems on Disaster Response Accuracy with Coordination Effectiveness as a Mediating Variable at the Regional Disaster Management Agency (BPBD) of Bandar Lampung City - Dera Ika Sari; Febrianty; Reza Hardian Pratama (Yayasan Multidimensi Kreatif, 2026)
Disaster response accuracy is an important indicator of the success of a disaster management organization. This study aims to analyze the influence of human resource competency, leadership style, and communication systems on disaster response accuracy, with coordination effectiveness as a mediating variable at the Bandar Lampung City BPBD. The study used a quantitative approach using the Partial Least Square Structural Equation Modeling method. Data were collected through questionnaires from BPBD employees in Bandar Lampung City. The results show that human resource competency and communication systems have a significant positive effect on coordination effectiveness and disaster response accuracy. Coordination effectiveness also significantly influences disaster response accuracy and mediates the influence of human resource competency and communication systems. Conversely, leadership style has no significant direct or indirect effect on disaster response accuracy. The study emphasized that strengthening human resource competency, communication systems, and organizational coordination are priorities for improving the quality of regional disaster response. These findings provide theoretical and practical implications for the development of regional disaster management in Indonesia today.